Immersive Technology for History Learning in Museums: A Systematic Literature Review and Implications for Yogyakarta Indonesia - Baihaqie, Muhammad Faruq Jabbar; Sudrajat, Ajat (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
technology for history education within museum environments. A Systematic Literature Review (SLR) was performed following the PRISMA 2020 guidelines to promote transparency and replicability. Following a rigorous screening process of 158 initial records, a final corpus of 16 high-quality empirical articles indexed in Scopus Q1 and Q2 journals published between 2019 and 2024 was selected for qualitative thematic synthesis. The findings indicate that while immersive tools, such as Virtual Reality (VR) and Augmented Reality (AR), have the potential to enhance learners' historical empathy and cognitive retention, their efficacy within Global South landscapes such as Yogyakarta is highly contingent upon a critical decolonial calibration of the socio-technical subsystem to safeguard local epistemologies against Western-centric digital biases; consequently, these technologies do not constitute a panacea for pedagogical challenges. The primary obstacle identified is the alignment gap between technological affordances and instructional design: while immersive hardware has reached technical maturity, pedagogical integration frameworks in museum environments remain underdeveloped. In terms of practical and social implications, this study underscores that professional focus must shift from mere technological novelty toward systemic staff development and the structural weaving of digital tools into the existing history curriculum. Ultimately, optimising these interactive learning spaces provides a sustainable, decolonised digital heritage roadmap that empowers regional educators and curators to integrate global technological innovations while firmly anchoring the social subsystem within localised epistemologies; this adaptive framework ensures that historical consciousness is fostered and cultural transmission is safeguarded within regional centres such as Yogyakarta without succumbing to Western-centric technological biases in the digital age.